The Clash of Mechanical and Electrical Size‐Effects in ZnO Nanowires and a Double Power Law Approach to Elastic Strain Engineering of Piezoelectric and Piezotronic Devices. (19th August 2014) - Rinaldi, Antonio; Araneo, Rodolfo; Celozzi, Salvatore; Pea, Marialilia; Notargiacomo, Andrea
<x xml:space="preserve">Abstract</x> The piezoelectric performance of ultra‐strength ZnO nanowires (NWs) depends on the subtle interplay between electrical and mechanical size‐effects. "Size‐dependent" modeling of compressed NWs illustrates why experimentally observed mechanical stiffening can indeed collide with electrical size‐effects when the size shrinks, thereby lowering the actual piezoelectric function from bulk estimates. "Smaller" is not necessarily "better" in nanotechnology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>